Estabilidade oxidativa de linguiça tipo Toscana com extrato liofilizado de casca de romã (punica granatum L.) - Zago, Gilberto Rogério (2018)
Natural and functional ingredients progressively gain the preference of consumers and researchers, serving as an alternative to conventional food additives. Natural antioxidants stand out as a promising alternative to the synthetic ones, and may present equivalence or better characteristics for the control of alterations in meat products, such as lipid oxidation, considered one of the main causes for the reduction of product lifetime and the rejection of consumption of these foods. Sausages are among the most consumed processed meat products, because of the ease of preparation and consumption. It is an high profitability product, which adds value to the raw material for the meat processing industries. The fruits stand out with the highest concentrations of antioxidant compounds, distributed in the pulp,seed and peel. Both during in natura consumption as in the fruit processing industry, parts such as seeds and peels are considered tailings. Studies carried out with residues of several fruits show that the pomegranate (Punica granatum L.) is among the fruits that present high concentrations of phenolic compounds of antioxidant capacity, and the bark comprises approximately 50% of the fruit (including the internal membrane network). For these reasons, the characterization and valorization of these co-products is necessary, reducing production costs and minimizing the environmental liability, through the reuse of their compounds in other foods, such as sausages. The freeze-dried extract of pomegranate peel (ELCR) presented yield of 18.96% in relation to the total crude peel powder used in the extraction and lyophilization process, with antioxidant activity of 98.7% (ABTS) and 90.21% (DPPH). From the stratification and characterization of antioxidant compounds, four Tuscan-style fresh sausage formulations were produced: a control sample with addition of 0.025% sodium erythorbate (ES) and lyophilized pomegranate peel extract at concentrations of 0.025% (ELCR1), 0.050% (ELCR2) and 0.1% (ELCR3). After the sausage making process, treatments were vacuum packed and stored at 5 ± 1°C under artificial lighting of 12 hours per day, simulating a supermarket shelf, and evaluated at the 1st, 15th and 30th days. The color coordinate L* presented slight darkening and a * differed (p <0.05) between the extracts ELCR2 and ELCR3 in relation to the ES, while b* showed no difference. The peroxide index presented a distinct behavior in the treatments, with little significance (p> 0.05). The values of TBARS remained below the oxidative rancidity detection range, and the addition of the freeze-dried extract of pomegranate peel was significant (p <0.05) when compared to ES. There were no significant lipid changes during the storage period. The sensorial analysis did not identified differences (p> 0.05) between the formulations with sodium erythorbate and lyophilized pomegranate peel extract, with color and flavor evaluation between 7 (I moderately liked it) and 8 (I liked it a lot). The freeze-dried extract of pomegranate peel had antioxidant effect and can be used in delaying lipid oxidation in Tuscan-style sausages.